Les Bases Azotées (bases nucléiques) dans les Réactions Multi-composants: Synthèse et Étude Biologique de Nouveaux Purines et Pyrimidines Fusionnées - عدايكه شيماء (université d'eloud, 2025)
الملخص: يهدف هذا العمل إلى تحضير وتوصيف مجموعة من المركبات الحلقية غير المتجانسة التي تحتوي على حلقات أساسية مثل البيريميدينوالبيورينوالبيرولوالبيرولو-بنزإيميدازول، وذلك باستخدام تفاعلات متعددة المركبات في خطوة واحدة. وقد تميزت هذه المركبات بخصائصها البيولوجية المتنوعة. تم التعرف على بنية المركبات المحضّرة بواسطة استخدام تقنيات التحليل الطيفي المختلفة مثل مطيافية الأشعة تحت الحمراء، مطيافية الرنين النووي المغناطيسي للبروتون والكربون، وتحليل العنصري. كما تم تقييم الفعالية المضادة للميكروبات لخمسة سلالات بكتيرية وفطري واحد باستخدام طريقة الانتشار الاجار بواسطة بئر، فتبين ان جميع المركبات المحضرة تمتلك فعالية ملحوظة ضد بعض السلالات البكتيرية واضافة الى فعالية جيدة ضد الفطر المبيضية البيضاء. كما قدرت الفعالية المضادة للأكسدة بثلاث طرق كيميائية أهمها طريقة اختبار الـDPPHوالـABTSواختبار القدرة الارجاعيةلموليبدات الفوسفات (PM) وقد تبين ان المركبات تمتلك فعالية مضادة للاكسدة وبعضها تفوقت على الشاهد المرجعي فيتامين سي. Abstract: This work aims to synthesize and characterize a series of heterocyclic compounds containing key rings such as pyrimidine, purine, pyrrole, and pyrrolo-benzimidazole, using one-pot multicomponent reactions. These compounds exhibited diverse biological properties. The structures of the synthesized compounds were identified using various spectroscopic techniques, including infrared spectroscopy (IR), proton and carbon nuclear magnetic resonance spectroscopy (¹H and ¹³C NMR), and elemental analysis. The antimicrobial activity was evaluated against five bacterial strains and one fungal strain using the agar well diffusion method. The results showed that all synthesized compounds exhibited noticeable activity against certain bacterial strains, as well as good activity against the fungus Candida albicans. The antioxidant activity was also assessed by three chemical methods: the DPPH radical scavenging assay, the ABTS assay, and the phosphomolybdate (PM) reducing power assay. The results revealed that the compounds possess antioxidant activity, with some showing higher activity than the reference standard vitaminC.
أطروحة دكتوراء
Keywords: تفاعلات متعددة المركبات; بيريميدين; بيورين; بيرول; بيرولو-بنزإيميدازول; فعالية مضادة للميكروبات; فعالية مضادة للأكسدة